Dynamics and ecological distributions of the Archaea microbiome from inland saline lakes (Monegros Desert, Spain). Issue 3 (1st February 2020) - Menéndez-Serra, Mateu; Ontiveros, Vicente J; Triadó-Margarit, Xavier; Alonso, David; Casamayor, Emilio O
ABSTRACT: We characterized the rich Archaea microbiome of shallow inland lakes (Monegros Desert, NE Spain) by 16S rRNA gene tag sequencing covering a wide salinity range (0.1%–40% w/v) along 3 years. Up to 990 operational taxonomic units (OTUs; >97% identity) were detected allocated in 14 major archaeal phyla and heterogeneously distributed along the salt gradient. Dynamics and idiosyncratic ecological distributions were uncovered for the different phyla. A high genetic richness was observed for Woesearchaeota and Pacearchaeota (>370 OTUs each), followed by Halobacteria (105), Nanohaloarchaeota (62) and Thermoplasmata (19). Overall, the distribution of genetic richness was strongly correlated with environmental niche amplitude, but not with occurrence. We unveiled high occurrence for a very rich Woesearchaeota assemblage, and an unexpected positive correlation of Pacearchaeota abundance with salinity at >15% dissolved salt content. The estimated dynamic behaviour (temporal 'turnover' rates of presence/absence data) unveiled Thaumarchaeota and Halobacteria as the most dynamic groups, and Aenigmarchaeota and Thermoplasmata as the most stable. The DPANN Pacearchaeota, Woesearchaeota, and Nanohaloarchaeota showed intermediate rates, suggesting higher resilience to environmental perturbations. A rich and dynamic Archaea microbiome was unveiled, including unseen ecological traits for relevant members of the still largely unknown DPANN group, supporting a strong ecological differentiation between Pacearchaeota and Woesearchaeota. Abstract : Dynamics and idiosyncratic patterns of ecological distributions were unveiled for the Archaea microbiome of inland saline lakes from one of the most arid regions in Europe.